Clinical utility of D-Dimer Point-Of-Care assay analyzers for exclusion of pulmonary thromboembolism in patients with COVID-19 - Roberto (2020)
Introduction: Acute pulmonary thromboembolism is a potentially fatal disease and the prevalence among patients infected with OVID-19 has increased to require laboratory and imaging examinations, which are not always readily available. D-Dimer levels may be particularly useful for diagnostic exclusion. Objective: To evaluate the clinical utility of D-Dimer POC assay analyzers to rule out the diagnosis of pulmonary thromboembolism in adult patients diagnosed with COVID-19. Method: Systematic review and meta-analysis. The technology evaluated was the D-Dimer Point-Of-Care assay analyzer. To combine the effect estimates whose measurement was the difference between the means, the random effect model was used. Results: 10 studies were included that evaluated 14 Point-Of-Care analyzers compared to the Enzyme Linked Immunosorbent Assay. All the Point-Of-Care analyzers evaluated had sensitivity and negative predictive value higher than 95 and 97% respectively with an average return time of 95 minutes less. Conclusion: The evidence suggests that the use of Point-Of-Care analyzers for D-Dimer has clinical utility to rule out cases of pulmonary thromboembolism and other thromboembolic complications in patients with COVID-19 in emergency room or Primary Care units.